Characterization of the nano-sized fraction of particles in food additives E174, E175 and E171 - Eveline Verleysen (2nd nano in Belgium workshop, 2018)
presentation at the 2nd Workshop 'Nano in Belgium'
Keywords: Food Additives; nanomaterials